Comunicação acústica e aspectos reprodutivos em Hypsiboas caingua (Carrizo, 1990) (Anura: Hylidae) no sul do Brasil. - Campos, Renata Mayara (2015)
The acoustic communication is the main strategy used during reproduction by anuran species, and plays an important role in attracting females, social organization, recruiting individuals for the choir, in maintaining the spacing between males and defense of the territory. Changes in vocalizations may occur due to environmental factors, morphological characteristics of males, and/or because of the social context. The study aimed to describe the vocal repertoire of Hypsiboas caingua and investigate whether there is influence of temperature, relative humidity, the morphological characteristics and the distance between males in their acoustic parameters. Additionally, it also provides information, not yet described, on the reproductive behavior of the species. Observations were carried out during the months from december 2013 to february 2014 and from october 2014 to march 2015, in swamps areas in the municipality Tuneiras do Oeste, northwest of Parana state. Calls of 25 individuals were analyzed, totaling 183 recordings. Recorded males emitted two distinct vocalizations: advertisement and aggressive calls. The acoustic parameters of the advertisement and aggressive calls differed one each other and varied among individuals. For the advertisement call the dominant frequency and the interval between calls were positively correlated with relative humidity; the mass of males and snout-vent length (SVL) negatively with the interval between notes; and the SVL and the size of the individuals positively with the duration of the note B. To aggressive call, only the mass was negatively correlated to the call duration. The spectral parameters of the advertisement call varied less than the temporal, both inter- and intra-individual and were classified as static or intermediaries, while temporal parameters as dynamics. To aggressive call, all inter-individual coefficients of variation were statics, whereas for intra-individual coefficient, only the dominant frequency was static and other variables, dynamics. The parameters of the advertisement call (dominant frequency, call duration and interval between calls) may perform best for specific recognition between individuals than the aggressive call parameters, where only the dominant frequency varied more among individuals than intra-individually.